Integrative role of KM infrastructure and KM strategy to enhance individual competence. Issue 3 (10th August 2015) - Kushwaha, Pooja; Rao, M.K.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to explore knowledge management (KM) literature to understand further the inter-relationship among KM infrastructure (KMI), KM strategy (KMS), KM process (KMP) and individual competence (IC), which are considered very much essential for achieving a heightened competence at an individual level. In the present scenario, knowledge intensive organizations are striving highly to manage competitiveness for their survival in the market. The role of knowledge capability is very much pivotal in ensuring the success of knowledge process implementation. Design/methodology/approach – A methodical review has been carried out of empirical and conceptual articles to justify the linkages among KMI, KMS, KMP and IC, particularly accessed through sources such as Pro Quest, EBSCO host, Google Scholar and other e-databases. This review integrates a conceptual framework to explore the relationship among the aforesaid constructs. Findings – This study provides valuable insight into the role of KMI and KMS in enabling various KM processes. It also contributes significantly to organizations by helping them to integrate KM processes so as to enhance IC. Research limitations/implications – This paper provides helpful suggestions to drive the KMPs by facilitating suitable congruence of infrastructure capabilities and KMSs within organizations. Further, this study would also be helpful in enhancing IC along with organizational competence. Study limitations are also discussed. Originality/value – This paper contributes to knowledge and competence management literature by adding the fact that KMI and KMS both precede KMP for better outcomes at an individual level.